Understanding the Pathogenesis of Gestational Hypothyroidism - Mallawa Kankanamalage, Oshini; Zhou, Qiongjie; Li, Xiaotian (Frontiers in Endocrinology, 2021)
Pregnancy is a complex state with many endocrinological challenges to a woman’s physiology. Gestational Hypothyroidism (GHT) is an emerging condition where insufficiency of the thyroid gland has developed during pregnancy in a previously euthyroid woman. It is different to overt hypothyroidism, where marked elevation of thyroid-stimulating hormone with corresponding reduction in free thyroxine levels, is well known to cause detrimental effects to both the mother and the baby. During the past couple of decades, it has been shown that GHT is associated with multiple adverse maternal and fetal outcomes such as miscarriage, pre-eclampsia, placental abruption, fetal loss, premature delivery, neurocognitive and neurobehavioral development. However, three randomized controlled trials and a prospective cohort study performed within the last decade, show that there is no neurodevelopmental improvement in the offspring of mothers who received levothyroxine treatment for GHT. Thus, the benefit of initiating treatment for GHT is highly debated within the clinical community as there may also be risks associated with over-treatment. In addition, regulatory mechanisms that could possibly lead to GHT during pregnancy are not well elucidated. This review aims to unravel pregnancy induced physiological challenges that could provide basis for the development of GHT. During pregnancy, there is increased renal clearance of iodine leading to low iodine state and elevated estrogen levels leading to increase in circulating thyroglobulin thus, low free thyroxine level. Moreover, placenta secretes compounds such as human chorionic gonadotropin (hCG), placental growth factor (PIGF) and soluble FMS-like tyrosine kinase-1 (s-Flt1) that could affect the thyroid function. In turn, the passage of thyroid hormones and iodine to the fetus is highly regulated within the placental barrier. Together, these mechanisms are hypothesized to contribute to the development of intolerance of thyroid function leading to GHT in a vulnerable individual.